UJI SENSITIVITAS EKSTRAK BAWANG PUTIH (ALLIUM SATIVUM) TERHADAP PERTUMBUHAN BAKTERI ESCHERICHIA COLI - Afriansya, Roni (JURNAL MEDIA KESEHATAN, 2014)
An Escherichia coli bacterium is normal flora bacteria in human body. The excess of bacteria can cause diseases. Garlic has allicin compound, which known as antimicrobial compound.. The research a purpose to determine the antibacterial activity of garlic against the bacteria Escherichia coli at a concentration of garlic and what was the most powerful (effective) hinders the growth of the bacterium Escherichia coli. The research was a laboratory experiment with antimicrobial testing using paper disc diffusion method. Garlic extract was made by the process of maceration. Maceration process conducted over 5 days. Garlic extracted and then tested on the growth of Escherichia coli with three repetitions. Observation was made after 1x24 hours. Then observed a clear zone was formed, the zone was measured by using a ruler. Results of the research noted that garlic extract has the ability to inhibit the growth of bacteria Escherichia coli and seen a proportional relation-ship in each other, concentration of garlic extract become greater as inhibiting the growth of the bacterium Escherichia coli does so. The most effective concentration to inhibit the growth of Escherichia coli bacteria was garlic extract concentration of 75 % with an average diameter of 10.66 mm zone of inhibition and concentration of 100% with an average inhibition zone diameter of 13.33 mm. Garlic can be used as medicine of natural materials dan consume garlic regularly can prevent the growth of escherichia coli bacteria that can not controlled in the body.